2010
DOI: 10.1103/physrevb.82.075403
|View full text |Cite
|
Sign up to set email alerts
|

Coherent spin manipulation in an exchange-only qubit

Abstract: Initialization, manipulation, and measurement of a three-spin qubit are demonstrated using a few-electron triple quantum dot, where all operations can be driven by tuning the nearest-neighbor exchange interaction. Multiplexed reflectometry, applied to two nearby charge sensors, allows for qubit readout. Decoherence is found to be consistent with predictions based on gate voltage noise with a uniform power spectrum. The theory of the exchange-only qubit is developed and it is shown that initialization of only t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
306
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 238 publications
(311 citation statements)
references
References 23 publications
4
306
0
1
Order By: Relevance
“…The name was coined by Kastner et al [20] after the discovery of quantized electronic levels inside the QDs. The amount of experiments performed in QDs and the variety of phenomena with a straight correlation to those found in atoms increased enormously over the years [21][22][23][24][25][26][27][28][29] and was mainly motivated by the vast range of technological applications of QDs as 07002-p.4…”
Section: Icec In Quantum Dotsmentioning
confidence: 99%
“…The name was coined by Kastner et al [20] after the discovery of quantized electronic levels inside the QDs. The amount of experiments performed in QDs and the variety of phenomena with a straight correlation to those found in atoms increased enormously over the years [21][22][23][24][25][26][27][28][29] and was mainly motivated by the vast range of technological applications of QDs as 07002-p.4…”
Section: Icec In Quantum Dotsmentioning
confidence: 99%
“…Three coherently coupled quantum dots with three spins attracted interest in the hope to construct a qubit using purely electrically gated manipulations [9,10]. Most recently, for a triple quantum dot (TQD) structure it was shown that bipolar spin blockade can become a relevant quantum coherent mechanism [11].…”
Section: Introductionmentioning
confidence: 99%
“…Here we examine the validity range of the Gaussian approximation, as the number of fluctuators is increased, and its dependence on the number of control pulses. As current experimental efforts are focused on more complicated QD structures, such as two coupled double QDs, 26,35 and three-spin qubits in triple-dots, [36][37][38] the resulting larger devices are expected to have a noisier charge environment. Understanding how qubit decoherence scales with the number of TLFs is therefore important.…”
Section: Introductionmentioning
confidence: 99%